Medullary Pancreatic Carcinoma Due to Somatic POLE Mutation: A Distinctive Pancreatic Carcinoma With Marked Long-Term Survival. Issue 7 (August 2020) - Kryklyva, Valentyna; ter Linden, Esther; Kroeze, Leonie I.; de Voer, Richarda M.; van der Kolk, B. Marion; Stommel, Martijn W.J.; Hermans, John J.; Luchini, Claudio; Wood, Laura D.; Hruban, Ralph H.; Nagtegaal, Iris D.; Ligtenberg, Marjolijn J.L.; et al.
Abstract : Abstract: Medullary pancreatic carcinoma (MPC) is a rare histological variant of pancreatic ductal adenocarcinoma (PDAC). Because of its rarity, data on the molecular background of MPC are limited. Previous studies have shown that a subset of MPCs is microsatellite instable due to mismatch repair deficiency. Here, we present a unique case of a female patient in her 60s who is a long-term survivor after surgery for pancreatic cancer. The patient had a microsatellite stable MPC with a somatic mutation of the polymerase epsilon gene ( POLE ). Both microsatellite instable and POLE -mutated cancers are usually associated with high tumor mutational burden and antigen load, resulting in a prominent antitumor immune response and overall better survival. The current case illustrates that, in addition to mismatch repair deficiency, MPC can develop because of a somatic POLE mutation, resulting in a tumor with a high tumor mutational burden and leading to a better prognosis compared with conventional PDAC. This new finding may have important implications in the management of patients with MPC and calls for further studies on the role of POLE in PDAC. Abstract : Supplemental digital content is available in the text.